Is Hamlet Scandinavian Crime Fiction? - Klusoňová, Markéta (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
This paper combines two of the suggested topics: “law as an instrument of ideology” and “ideological interpellation through law” as it explores whether or not it is possible to use literary fiction as part of an argument in legal argumentation. The use of such an argument is strongly connected with an attitude of state to art, culture and values included both in art and law. Art as a part of a socio-cultural system is one of the material sources of law so it would be natural to admit it in just judicial decision. Unfortunately it is not typical for law to use such relationships between art and law to make judicial decisions better or at least more persuasive. It may be caused by the fact that the choice of what literary fiction is suitable for legal argumentation and which is not can be seen as a kind of ideology. Therefore the state determines which art is “good enough” to be a part of legal reasoning. Usually it differs between “high art” and “mass culture.” It results in a form of “labelling” of art. Unfortunately, by evaluating art in such a manner each state manifests itself as almost a totalitarian one. Socialist realism was a very expressive example. So it is not a matter for the democratic state to decide which piece of art is capable to influence law, is it? In this contribution I will emphasize Žižek’s critique of ideology in order to deal with ideology in argumentation by literary fiction in law. Besides that I will draw inspiration from Law and Literature movements. The aim of my paper is to explain how literary fiction can be used as a legal argument in a proper way as a necessary social appeal through law.
Keywords: law as an instrument of ideology; ideological interpellation through law; legal argumentation